Jenis Kesalahan Pada Pembuktian Matematis - Cyntia Suarni Arifin; Farizi Aqfi; Rusi Ulfa Hasanah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study aims to find out and describe the types of errors in mathematical proof. This research method is based on literature review. The stages of this literature review are data collection, data reduction, data display, discussion and conclusions. The research results show that of the 6 articles published from 2014-2023 regarding types of errors in mathematical proof, 6 articles were found that were in accordance with the research variables. The novelty of this research is that there is a connection between one article and other articles that discuss the same topic. The conclusion from this data is that there are many mistakes made by students when working on questions that require mathematical proof. The forms of errors made by students include conceptual errors, principle errors, calculation errors, language interpretation errors, and errors when drawing conclusions.